2018
DOI: 10.4103/jfcm.jfcm_126_17
|View full text |Cite
|
Sign up to set email alerts
|

How does the utilization of diabetes dietitian and educator service in Saudi Arabia affect glycemic outcomes?

Abstract: BACKGROUND:Despite the acknowledgment that the services of diabetes educator and dietician affect outcome, the level of utilization of these services in the Saudi Arabian public health-care system is not known. The aims of the study were to establish the percentage of patients with diabetes mellitus (DM) followed up by a diabetic educator and a dietician in a tertiary center in Saudi Arabia and associations between follow-up by a diabetic educator and a dietician and glycemic control.MATERIALS AND METHODS:This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…The results showed that 54% of the participants intended to use the CC method for DM management, visited a dietician and were frequently taught about the CC method. However, this trend contrasts with other SA studies, in which 18% of participants used the CC method18 and 19.8% reported visiting a dietitian 23. The reason for these differences may be that the UDC, where the study was conducted, is a long-established, specialised diabetes centre in Riyadh that provides different services and treatment options for DM management, including intensive insulin therapy with multidisciplinary teams.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The results showed that 54% of the participants intended to use the CC method for DM management, visited a dietician and were frequently taught about the CC method. However, this trend contrasts with other SA studies, in which 18% of participants used the CC method18 and 19.8% reported visiting a dietitian 23. The reason for these differences may be that the UDC, where the study was conducted, is a long-established, specialised diabetes centre in Riyadh that provides different services and treatment options for DM management, including intensive insulin therapy with multidisciplinary teams.…”
Section: Discussionmentioning
confidence: 77%
“…However, this trend contrasts with other SA studies, in which 18% of participants used the CC method 18 and 19.8% reported visiting a dietitian. 23 The reason for these differences may be that the UDC, where the study was conducted, is a long-established, specialised diabetes centre in Riyadh that provides different services and treatment options for DM management, including intensive insulin therapy with multidisciplinary teams. Furthermore, the mean knowledge score was 23.01±7.3, which is consistent with the mean knowledge score of the original questionnaire (23.9±8.3).…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of two investigations (Al-Shahrani, 2018;Alshareef et al, 2018), most previous have shown a similar effect on HbA1c levels (ranging from 0.6 to 0.93) (Dinar et al, 2019;International Diabetes Federation, 2017;Plank et al, 2004;Rashid, 2012). Our achieved net effect on HbA1c was even more favourable than those observed in these studies, likely due to the strength and routine nature of our extensive educational sessions.…”
Section: Discussionmentioning
confidence: 95%
“…[28] In another cross-sectional study of 490 DMT2 patients enrolled in the public health-care institution in Riyadh, HbA1C levels were significantly lower in patients who had a periodical follow-up with a dietitian ( P < 0.0001). [29]…”
Section: Discussionmentioning
confidence: 99%